OUTBREAKS OF SCARLET FEVER IN KINDERGARTENS IN BELGRADE - Giljaca, Sonja; Maris, Slavica; Rancic, Natasa; Mrvaljevic, Milutin; Mrvaljevic, Zorica (HEALTH CARE, 2022)
Introduction/Aim: Scarlet fever is mostly a childhood disease and in about 90% of cases it occurs in children younger than 10 years. Outbreaks of scarlet fever always occur in children’s collectives (kindergartens, schools and institutions for children). The aim of this paper is to analyze the epidemiological characteristics of scarlet fever epidemics in kindergartens in Belgrade during the five-year period (2016-2020). Methods: Data about new cases of scarlet fever were collected for the observed period from the City Institute for Public Health Belgrade. The data sources used are: epidemiological questionnaire, medical documentation and laboratory results. The presence of β-hemolytic streptococcus group A in diseased children was proven by bacteriological analysis of throat and nose swabs. General and specific incidence rates were used in the data analysis. Results: During the observed five-year period, 30 epidemics of scarlet fever were registered, in which a total of 114 children from 23 Belgrade kindergartens became ill. In 2017, there were 12 epidemics with a total of 49 cases, which represents the largest total number of cases in one year. In the period from 2016 to 2020, the highest number of patients among all patients with scarlet fever was among children aged 4 years (33.3%), and the lowest among children aged 2 years (1.7%). There were slightly more sick boys (57.9%) than girls (42.1%). The highest average five-year incidence rates for scarlet fever were recorded at the age 1-4 (383.7 per 100,000) and 5-9 years (262.8 per 100,000), and the lowest were in persons aged 15 and over. About 1/3 of sick children were registered in the municipality of New Belgrade, and about 1/3 of sick children were registered in the period of early spring (March-April). Conclusion: Respect and timely application of anti-epidemic measures contribute to the successful cessation of further spread of infection (disease reporting, isolation, treatment of sick children, as well as stricter hygiene measures and ongoing disinfection).